Statehood and lordship in 'Scotland' before the mid-twelfth century - Broun, Dauvit (The Innes review, 2015)
Discussions of medieval statehood are guided (explicitly or implicitly) by the work of social scientists. The exiguous sources for studying Scotland in the central middle ages offers an opportunity to approach the question of statehood in a new way that depends more on the creative potential of arts and humanities. Social sciences remain crucial for understanding statehood. Instead of being guided by them during the research, however, the medieval material can itself become the basis for a dialogue with formulations of statehood by social scientists, or by historians drawing on social science. The focus is on Scotland' (the country between the Forth and the Spey), examining the basis of secular authority in local lordship, and how this underpinned the mobilisation of society for the sake of safeguarding its peace and security. This includes a consideration of the power of lordly kindreds, the lands assigned to the offices of mormaer and king, and the changing relationship of lords to individual settlemen...